Does Emergency Department Use for Alcohol and Other Drug Use Cluster Geographically? A Population-Based Retrospective Cohort Study. (28th July 2016) - Newton, Amanda S.; Shave, Kassi; Rosychuk, Rhonda J.
ABSTRACT: Purpose : To identify geographic areas in Alberta, Canada with higher numbers of adolescents with an emergency department (ED) presentation for a mental or behavioral disorder secondary to alcohol and other drug use. Methods : A population-based cohort analysis of ED visits ( n = 7787) by adolescents aged 15–17 years ( n = 7238) during 2002–2011. We calculated sex-adjusted directly standardized rates (DSRs) and identified space-time clusters in health zones (North, Edmonton, Calgary, Central, and South). Results : The North zone had higher DSRs compared to other areas. Clusters were identified in: (1) North, Edmonton, and northwest Central zones [relative risk (RR: 1.54; from 2004 to 2008); (2) western South and southern Calgary zones (RR: 1.58; from 2007 to 2011); and (3) northern South zone (RR: 2.38; from 2006 to 2007). Conclusions : The spatial scan can identify geographic areas of high health care use for specific health conditions. These results, in turn, can be used to inform health resource planning.